Sterility of Gauze Packed in One and Three Layer Layer Parchment Paper - Saskia Biyakto Putri; Endang Sri Lestari; Vincentia Rizke Ciptaningtyas (Sains Medika, 2017)
Intoduction: Sterile gauze is one of the medical devices that are often used to prevent infection. Several things, one of them is materials for packaging, can affect the sterility of gauze. Parchment paper is one of the packaging materials for sterilization. The study was done to analyze the sterility of gauze packed with parchment paper one layer and three layers on the growth of microorganism.